Progress in the study of reproductive toxicity of platinum-based antitumor drugs and their means of prevention - Jin, Zhan; Zhao-Xia, Liu; Fan-Ke, Peng; Wen-Juan, Zhang; Min-Li, Wei; Han-Yi, Zeng (Frontiers in Pharmacology, 2024)
Platinum-based antitumor drugs are broad-spectrum agents with unique mechanisms of action. Combination chemotherapy regimens based on platinum drugs are commonly used in cancer treatment. However, these drugs can cause various adverse reactions in the human body through different routes of administration, including reproductive toxicity, genetic toxicity, and embryonic developmental toxicity. Preventing adverse effects is crucial to enhance patients' quality of life and reduce healthcare costs. This article discusses the types and developmental history of antitumor active platinum compounds, their mechanisms of action, routes of administration, and their potential reproductive, genetic, and embryonic developmental toxicity. This text explores preventive measures based on animal experimental results. Its aim is to provide references for personalized treatment and occupational protection when using platinum drugs. The continuous progress of science and technology, along with the deepening of medical research, suggests that the application of platinum drugs will broaden. Therefore, the development of new platinum drugs will be an important direction for future research.In the 1960s, Rosenberg and colleagues made the initial discovery that platinum (Pt) ions can suppress cell division by conducting an experiment on E. coli using a direct current electric field [1] . Subsequently, their findings led to the exploration of a new area of research on the antitumour effect of Pt complexes by oncology researchers.